Beyond Health, Beyond Choice : Breastfeeding Constraints and Realities - Labbok, Miriam H.; Hausman, Bernice L.; Smith, Paige Hall (Book collections on Project MUSE., 2012)
Beyond Health, Beyond Choice is a multidisciplinary collection of essays written by thirty-seven contributors that examines the role of feminist theory in the promotion of breastfeeding by public health authorities. Essays are arranged thematically and consider breastfeeding in relation to health care; work and family; embodiment (specifically breastfeeding in public); economic and ethnic factors; guilt; violence; and commercialization.